Cerebral critical closing pressure in hydrocephalus patients undertaking infusion tests. (August 2015) - Varsos, Georgios V.; Czosnyka, Marek; Smielewski, Peter; Garnett, Matthew R.; Liu, Xiuyun; Kim, Dong-Joo; Donnelly, Joseph; Adams, Hadie; Pickard, John D.; Czosnyka, Zofia
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Links between cerebrospinal fluid (CSF) compensation and cerebral blood flow (CBF) have been studied in many clinical scenarios. In hydrocephalus, disturbed CSF circulation seems to be a primary problem, having been linked to CBF disturbances, particularly in white matter close to surface of dilated ventricles. We studied possible correlations between cerebral haemodynamic indices using transcranial Doppler (TCD) ultrasonography and CSF compensatory dynamics assessed during infusion tests. Methods: We analysed clinical data from infusion tests performed in 34 patients suspected to suffer from normal pressure hydrocephalus, with signals including intracranial pressure (ICP), arterial blood pressure (ABP) and TCD blood flow velocity (FV). Cerebrospinal fluid compensatory parameters (including elasticity) were calculated according to a hydrodynamic model of the CSF circulation. Critical closing pressure (CrCP) was calculated with the cerebrovascular impedance methodology, while wall tension (WT) was estimated as CrCP-ICP. Closing margin (CM) was expressed as the difference between ABP and CrCP. Results: Intracranial pressure increased during infusion from 6.7 ± 4.6 to 25.0 ± 10.5 mmHg (mean ± SD; P < 0.001), resulting in CrCP rising by 22.9% (P < 0.001) and WT decreasing by 11.3% (P = 0.005). Closing margin showed a tendency to decrease, albeit not significantly (P = 0.070) due to rising ABP (9.1%; P = 0.005). Closing margin at baseline ICP was inversely correlated to brain elasticity (R = (0.358; P = 0.038), while being significantly different from zero for the whole duration of the tests (52.8 ± 22.8 mmHg; P < 0.001). Neither CrCP nor WT was correlated with CSF compensatory parameters. Discussion: Critical closing pressure increases and WT decreases during infusion tests. Closing margin at baseline pressure may act as an indicator of the cerebrospinal compensatory reserve.